2022
DOI: 10.1111/eci.13731
|View full text |Cite
|
Sign up to set email alerts
|

The advantages of physical exercise as a preventive strategy against NAFLD in postmenopausal women

Abstract: Background The prevalence and severity of nonalcoholic fatty liver disease (NAFLD) increase in women after menopause. This narrative review discusses the causes and consequences of NAFLD in postmenopausal women and describes how physical activity can contribute to its prevention. Methods The authors followed the narrative review method to perform a critical and objective analysis of the current knowledge on the topic. The Medical Subject Heading keywords ‘physical exercise’, ‘menopause’, ‘hormone replacement t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 201 publications
(354 reference statements)
0
9
0
2
Order By: Relevance
“…Visceral fat accumulation is one of the characteristics of FLD. Overweight, obesity, dyslipidemia, insulin resistance, type 2 DM, and sedentary behavior accompanied by lack of physical activity, which are closely related to factors of MetS, are the major causes of the increasing trend of NAFLD/MAFLD worldwide [ 60 ]. Therefore, in postmenopausal women, the rate of progression of NAFLD/MAFLD and the severity of the disease increase.…”
Section: Definition Of Menopause and Metabolic Disordersmentioning
confidence: 99%
See 3 more Smart Citations
“…Visceral fat accumulation is one of the characteristics of FLD. Overweight, obesity, dyslipidemia, insulin resistance, type 2 DM, and sedentary behavior accompanied by lack of physical activity, which are closely related to factors of MetS, are the major causes of the increasing trend of NAFLD/MAFLD worldwide [ 60 ]. Therefore, in postmenopausal women, the rate of progression of NAFLD/MAFLD and the severity of the disease increase.…”
Section: Definition Of Menopause and Metabolic Disordersmentioning
confidence: 99%
“…This is when obesity increases due to changes in lipid transport and lipid metabolism, and the distribution of fat from the subcutaneous to visceral adipose tissue changes, which increases the severity of NAFLD/MAFLD in postmenopausal women. Additionally, when estradiol-mediated gene expression of enzymes involved in lipid metabolism increases NAFLD/MAFLD susceptibility in postmenopausal women, they become more susceptible to NAFLD/MAFLD [ 59 , 60 ].…”
Section: Definition Of Menopause and Metabolic Disordersmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the practice of physical activity, it has been observed that different modalities, intensities and volumes of training can result in cardiometabolic improvement and prevention of the MUH phenotype [ 6 , 7 ]. Martinéz-Goméz et al [ 8 ], in a cohort study with individuals of both sexes and different BMI classes, identified an inverse association between the practice of leisure-time physical activity and the incidence of the MUH phenotype among those with MH normal weight and overweight.…”
Section: Introductionmentioning
confidence: 99%